2019
DOI: 10.15666/aeer/1702_36673680
|View full text |Cite
|
Sign up to set email alerts
|

Green Roof Plant Responses to Greywater Irrigation

Abstract: Water is an essential natural resource and is even known to be the cause of many wars of history. While people depend on it to survive, they also use it for everyday activities and several other purposes. As for plants, water is an essential factor, one they need for growth. Although irrigation is really important for certain agricultural plants, many criticise its water consumption especially on scientific platforms and media. This naturally pushes the world to find alternative ways to decrease the water cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Yet, there were no reported adverse effects on plants due to greywater for irrigation (Agra et al 2018 ). In a study for indicating the plants’ response to greywater irrigation, Yalcinalp et al ( 2019 ) compared two different greywater models and tap water for GR irrigation. They showed that the use of greywater provides more positive effects on plant growth compared to that of tap water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there were no reported adverse effects on plants due to greywater for irrigation (Agra et al 2018 ). In a study for indicating the plants’ response to greywater irrigation, Yalcinalp et al ( 2019 ) compared two different greywater models and tap water for GR irrigation. They showed that the use of greywater provides more positive effects on plant growth compared to that of tap water.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the use of greywater provides more positive effects on plant growth compared to that of tap water. Also, utilizing greywater can reduce the irrigation costs of the GR (Yalcinalp et al 2019 ). Hence, by using greywater in GRs, it is possible to sustain plant growth, reduce the use of potable water, and reduce demands on municipal wastewater treatment plants (Xu et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%